TOOLS FOR VISUALIZING TEXTUAL DATA (Bulletin of Innovative Research, 2026)
Visualization plays a crucial role in analyzing large volumes of textual data today. This article examines the main tools for text data visualization — both no-code and code-based solutions: R (ggplot2 and others), Tableau, and Python libraries (Matplotlib, Plotly). The advantages, disadvantages, and practical applications of these tools are analyzed through real-world examples.